2016
DOI: 10.1149/2.0641609jes
|View full text |Cite
|
Sign up to set email alerts
|

Facile Synthesis of Ca-Doped LaCoO3Perovskite via Chemically Assisted Electrodeposition as a Protective Film on Solid Oxide Fuel Cell Interconnects

Abstract: Interconnects in solid oxide fuel cells (SOFCs) serve two essential roles, namely, cell-to-cell electrical connection and the separation of fuel and oxidant gases. It is of practical significance to develop a protective coating that is capable of improving the surface stability of metallic interconnects while maintaining their electrical properties. Perovskite-type oxides are recognized as promising materials for protective coatings; however, it is difficult to fabricate high-density films by conventional powd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
13
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 38 publications
0
13
0
Order By: Relevance
“…In the CAED step, LaCo(OH) x is conformally formedo nt he carbon-coated LSM-YSZ electrode as follows.U pon cathodic polarization,t he pH near the LSM-YSZ electrode is drastically elevated owing to the electrochemical reduction of nitratespecies (NO 3 À ), which allows spontaneous chemical precipitation of LaCo(OH) x on the electrode (Figure 1b). [30][31][32] Figure 1b shows ap otentialv ersus time profile during aC AED process performed by using ac athodic current density of 1mAcm À2 for 6min. In the previous studies, we found that ah igherc urrent density (overpotential)c auses the formationo fl arge-scale agglomerates owing to severe hydrogen evolution, whereas a lower current density (overpotential) leads to uniform deposition at as lower rate.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…In the CAED step, LaCo(OH) x is conformally formedo nt he carbon-coated LSM-YSZ electrode as follows.U pon cathodic polarization,t he pH near the LSM-YSZ electrode is drastically elevated owing to the electrochemical reduction of nitratespecies (NO 3 À ), which allows spontaneous chemical precipitation of LaCo(OH) x on the electrode (Figure 1b). [30][31][32] Figure 1b shows ap otentialv ersus time profile during aC AED process performed by using ac athodic current density of 1mAcm À2 for 6min. In the previous studies, we found that ah igherc urrent density (overpotential)c auses the formationo fl arge-scale agglomerates owing to severe hydrogen evolution, whereas a lower current density (overpotential) leads to uniform deposition at as lower rate.…”
Section: Resultsmentioning
confidence: 99%
“…In the previous studies, we found that ah igherc urrent density (overpotential)c auses the formationo fl arge-scale agglomerates owing to severe hydrogen evolution, whereas a lower current density (overpotential) leads to uniform deposition at as lower rate. [30][31][32] Based on the preliminaryo ptimization study,inthis work, acathodic current density was selected in such aw ay that LaCo(OH) x could be conformally formedo n the carbon-coated LSM-YSZ electrode. The measured potentials ranged between À0.80 and À0.84 Vv ersus Ag/AgCl, which are much lower than the reduction potential of NO 3 À (À0.19 Vv s. Ag/AgCl).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations